FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI BALITA DI PMB HERASDIANA KOTA PALEMBANG TAHUN 2024 - Khoiriah, Annisa; Rosdiana, Meta; Mariyam, Nelly (LPPM STIKes Mitra Adiguna, 2025)
Malnutrition in toddlers is one of the problems considered important in the millennium development goals. In 2023, the prevalence of malnutrition was 13.0%. From the PMB Herasdiana Palembang Profile data, 1.92% of toddlers experienced malnutrition. The purpose of this study was to determine the Factors Related to Nutritional Status in Toddlers at PMB Herasdiana Palembang in 2024. This study used an analytical survey method with accidental sampling techniques and a cross-sectional approach, respondents in this study were mothers who had toddlers who came to PMB Herasdiana in Palembang in 2024, totaling 34 respondents. The nutritional status of toddlers was determined by weighing and the KMS book. The results of univariate analysis obtained the nutritional status of toddlers with nutritional status of toddlers lacking 20 (58.8%) and good nutrition 14 (41.2%), low maternal education 19 (55.9%) and high maternal education 15 (44.1%), unemployed mothers 14 (35.3%) and working mothers 20 (64.7%), and low family income 22 people (64.7%), and high family income 12 people (35.3%). The results of bivariate analysis with chi-square statistical test showed a significant relationship between maternal education and nutritional status of toddlers p Value < (0.02 <0.05), and there was a significant relationship between maternal occupation and family income, maternal occupation with p Value < (0.013 < 0.05), and family income p Value < (0.05 ?0.05).